Thermal Cyanobacteria from Panchor Hot Spring, Serian - Nur Afiqah, binti Abdul Rahim (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Cyanobacteria which also known as blue-green algae are ubiquitous, as they can be found in almost all aquatic environments such as marine, freshwater, brackish water and even hot spring. A study was conducted at Panchor Hot Spring, Serian in December 2013, January 2014 and March 2014 for documentation of its species composition of cyanobacteria. Samples of cyanobacteria were qualitatively collected for microscopic observation and identification from the pools of Panchor Hot Spring in the form of microbial mats on the water surface, samples in the water column and samples that attached on the wall of the pools and other substrates present. Live samples were collected for better identification. Results showed 16 species of cyanobacteria were found belonging to eight genera which were Aphanocapsa, Chroococcus, Lyngbya, Oscillatoria, Phormidium, Planktothrix, Pseudanabaena and Tychonema. Systematic accounts for classification, brief description and general environment for each species were discussed and documented. Based on the findings, Oscillatoria terebriformis was considered as dominant species while Oscillatoria nigra was occasionally found at Panchor Hot Spring.